2019
DOI: 10.35808/ijeba/199
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Corporate Hedging Policy: A Case Study from Indonesia

Abstract: Looking at general, the company will hedge when the amount of foreign debt rises along with fluctuations in foreign exchange rates. However, this is not the case with the non-financial sector companies in Indonesia Stock Exchange, which shows a decrease in the use of derivative instruments compared to financial sector companies during the period 2014-2016. Τhe study aims to analyze the effect of internal factors on hedging policies through the use of derivative instruments in nonfinancial companies in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 37 publications
6
13
0
1
Order By: Relevance
“…From the study result, Bartram (2008) proved that the cash flow indicators could measure forex exposure. This finding is similar to Cuestas, Huang and Tan (2018) and Wahyudi et al (2019) that also showed a significant relationship between cash flow indicators and forex exposure. However, Prasad and Suprabha (2015) claimed that although the cash flow method is an efficient tool for measuring forex exposure, most studies preferred using the capital market approach due to data availability.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…From the study result, Bartram (2008) proved that the cash flow indicators could measure forex exposure. This finding is similar to Cuestas, Huang and Tan (2018) and Wahyudi et al (2019) that also showed a significant relationship between cash flow indicators and forex exposure. However, Prasad and Suprabha (2015) claimed that although the cash flow method is an efficient tool for measuring forex exposure, most studies preferred using the capital market approach due to data availability.…”
Section: Introductionsupporting
confidence: 90%
“…Most of the past studies measured forex exposure using foreign sales (Afza & Alam 2011;Allayannis & Ofek 2001;Ameer 2010;Clark et al 2006;Jorion 1990;Judge 2006;Marshall, Kemmitt & Pinto 2013;Nydahl 1999;Vural-Yavas 2016;Wahyudi et al 2019;Wong 2000). There is a mixed result on foreign sales as forex exposure indicators, Wahyudi et al (2019) who referred to Ameer (2010) for the usage of foreign sales in measuring forex exposure found a contradicting result to Ameer (2010). One of the reasons for the insignificant effect is, measuring forex exposure solely on foreign sales might not capture the total amount of forex exposure as it will deduct foreign cash flows other than those due to operations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Working capital is defined as funds used to finance the company's daily operations. Every kind of management may include cash, banking, receivables, inventories and income management that is still acceptable (Wahyudi, Goklas, Rita, Hersugondo and Laksana, 2019). The availability of working capital funds needed by each company varies according to the type of business, as well as the management of the working capital.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…By identifying the overall supporting components of the BM, we can understand how BMs can build value propositions to generate profits using the required processes and resources (Johnson et al, 2008). A business model approach can be used to analyze the competitive structure and make strategic innovation decisions (Hamel, 2000;Wahyudi et al, 2019;Rupeika-Apoga et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%